2021
DOI: 10.3390/ijms22083969
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Challenges in Severe Eosinophilic Asthma: Differential Response to Anti-IL-5 and Anti-IL-5R Therapy

Abstract: Severe asthma greatly affects patients’ quality of life. Major advances have occurred in the management of severe eosinophilic asthma the past few years due to the new targeted biological therapies. There are three anti-IL-5 mAbs, mepolizumab, reslizumab and benralizumab. Despite the different mechanism of blocking IL-5 the clinical effects are quite similar as randomized controlled trials and real-life studies have shown. Moreover, there are reports of responding to one after failing to respond to another ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 65 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…Benralizumab combats the effect of over-activated IL-5 function by targeting the IL-5 receptor. It not only inhibits the function of the IL-5 receptor, but it can also direct the apoptosis process in eosinophils and basophils by recruiting NK cells [59]. Benralizumab application improved all patients' situations at three months and six months treatment in a recently published multicenter study involving 42 patients.…”
Section: The Application Of Monoclonal Antibodies In Patients With T2...mentioning
confidence: 99%
“…Benralizumab combats the effect of over-activated IL-5 function by targeting the IL-5 receptor. It not only inhibits the function of the IL-5 receptor, but it can also direct the apoptosis process in eosinophils and basophils by recruiting NK cells [59]. Benralizumab application improved all patients' situations at three months and six months treatment in a recently published multicenter study involving 42 patients.…”
Section: The Application Of Monoclonal Antibodies In Patients With T2...mentioning
confidence: 99%
“…Benralizumab has found to deplete peripheral blood basophils [ 114 ]. Oral corticosteroid use was also reduced with mepolizumab or benralizumab in comparison with placebo [ 19 , 27 , 30 , 105 , 113 , 114 , 115 , 116 , 117 ]. Despite their comparable effects, anti-IL-5 and anti-IL-5Rs have different mechanisms of action, and their effects vary depending on specific asthma endotypes.…”
Section: Biologic Agents Targeting Type 2 Inflammationmentioning
confidence: 99%
“…Lung eosinophilia induces severe asthma by promoting IL-5 signaling. Recent clinical progress has been made by the discovery of biological agents targeting IL-5/IL-5R, such as Mepolizumab, Benralizumab, and Reslizumab [56]. Randomized control studies (RCTs) revealed the efficacy of these agents against severe eosinophilic asthma [57][58][59].…”
Section: Type 2 Immune Responses In Arthritismentioning
confidence: 99%